Theoretical studies and vibrational spectra of 1H -indole-3-acetic acid: Exploratory conformational analysis of dimeric species - Lobayan, Rosana M. (2011)
Theoretical studies on 1H-indole-3-acetic acid (IAA) were performed to investigate the conformational properties of dimeric species and vibrational spectra. Experimental infrared spectra at 100 K and 297 K and Raman spectrum at 297 K were analyzed and compared against calculations performed at B3LYP/6-31G** level. A exploratory study of the conformational space of dimeric species was performed. Our analysis showed that dimeric forms predicted theoretically contribute distinctively to the assignments of experimental results. These structures are defined by the orientation of the acetyl moieties with respect to the plane of indole ring. The dimers are formed by two symmetrical IAA monomers (one of them with the acetyl moiety upward oriented, Re-face, and the other isomer having the acetyl moiety downward oriented, Si-face) in tail-to-tail way. The X-ray geometry and FTIR vibrational frequencies were compared with the results of DFT calculations. A conformational equilibrium involving the non-equivalent IAA dimers: CCT-CCT, A+A+T-A-A-T, A+A-T-A-A+T, and A+CT-A-CT was found. The relation of the conformational properties of the IAA molecule with the features of the vibrational spectra was described in detail. The band assignments were discussed as related to the conformations properties. Our analysis shows the significance of the theoretical study of the conformational space of the monomeric molecule in the rationalization of experimental results.